New records on Fomitiporia and Fuscoporia (Hymenochaetaceae) in areas of the Atlantic Forest in Northeastern Brazil: Fomitiporia and Fuscoporia in Northeast Brazil - Targino de Oliveira, Virton Rodrigo; Baptista Gibertoni, Tatiana (Lilloa, 2023)
During collections carried out in the Atlantic Forest in Northeastern Brazil, specimens belonging to Fomitiporia and Fuscoporia were collected. The morphological and molecular analyses of ITS and nLSU regions confirmed that they represent Fomitiporia conyana, Fo. maxonii, Fo. neotropica, Fuscoporia atlantica, Fu. formosana, Fu. licnoides and Fu. scruposa, some of them new records for areas of Atlantic Forest in Brazil as well as for the states of Alagoas, Bahia and Pernambuco.